Factors Affecting the Professional Satisfaction of School Teachers in Sri Lanka - Wanasinghe, W. M. Shaminda; Priyadarshani, H. D. C. (Advances in Social Sciences Research Journal, 2022)
The teacher is the principal inventor of the education system. This is because the basic foundation for producing the human resources required for a country is laid by the teacher. Therefore, the teacher needs to create an environment in which he can carry out his career in a more satisfying context. When the teacher is satisfied, the students who learn from him benefit from it. However, there are problems with the teacher's service due to factors such as criticism of human resources in Sri Lanka, high marks in exam failures, and over-emphasis on extra classes. Therefore, the main objective of this research paper was to study the level of professional satisfaction of teachers in government schools in Sri Lanka and the factors influencing it. The literature review also revealed that there were problems with teachers' professional satisfaction. The study was aimed at identifying the level of professional satisfaction of teachers, identifying specific factors affecting professional satisfaction, and making recommendations for enhancing professional satisfaction. The survey methodology of the quantitative research approach was used for the study. It was decided that the method would be more appropriate as it was an opinion poll. Although the total population of government school teachers working in Sri Lanka was limited to the public school teachers in the Kandy District as the sample selectable population. Accordingly, out of 15 randomly selected teachers in 15 schools in the Kandy District, 233 teachers were selected for random sampling. A questionnaire prepared using the Likert scale was used to collect the data online. The data obtained from it were analyzed according to the quantitative methodology. According to the data analysis, 34.76% of the respondents said that the overall sample was professionally satisfied and 37.76% said they were dissatisfied. Thus, a small number of respondents said they were not satisfied. It is also noteworthy that the response was moderate at 27.46%. Testing the level of professional satisfaction according to the variables revealed that the satisfaction level of female teachers was higher than that of male teachers. Professional satisfaction levels were also found to be higher for teachers in 1AB schools, for graduate teachers in terms of educational qualifications, and teachers less than 30 years of age. Factors influencing career satisfaction were also assessed. Accordingly, occupational safety, career development opportunities, training, and development were the top gainers. Also, promotions, salaries, and credit facilities were seen as the minimum attainment factors. Thus the following conclusions could be drawn. There was no significant change in teachers' professional satisfaction that different variations in occupational satisfaction could be observed depending on the background factors of teachers, and financial factors did not have such an impact on occupational satisfaction. Recommendations were made to provide continuous training opportunities, increase special focus on occupational safety, and involve teachers in the decision-making and management process by adopting a participatory management style in school. It can be pointed out that the service that a school can do to maintain a high level of professional satisfaction for the teacher. It is important to note that the benefits of developing a school teacher's satisfaction will be felt by students and ultimately the entire education system.